KEWAJIBAN MENUNTUT ILMU: Kajian Tafsir Tematik - Ilmi, Ziyadatul; Siham, Aqilla Armintya (Muta'allim: Jurnal Pendidikan Agama Islam, 2024)
The Humans and Jinn are commanded to worship Allah swt. And there is no way and no way to worship Allah swt. properly except with syar'i knowledge, namely the ladder to Allah swt. and he too is the way to His pleasure. Islam cannot be enforced except by knowledge. Islam circulates and is preached in the midst of society with knowledge, and Muslims are people of knowledge, because of all the rules and teachings contained in Islam is based on and based on knowledge. Al-Qur'an from beginning to end is a science that contains many lessons that very important and precious to us, and we are not allowed to talk about this religion except with knowledge. Science has a high position in Islam. Because of that people who have knowledge occupy a high position in the sight of Allah SWT. All Muslims are required to seek knowledge so that their faith does not go astray, their worship is correct, and their behavior is in accordance with the Shari'a. Seeking knowledge is one of the obligations for every Muslim as long as life is still conceived in the body. Abstrak Manusia dan Jin diciptakan untuk menyembah Allah swt. Dan tidak ada jalan serta cara untuk menyembah Allah swt. dengan baik kecuali dengan ilmu syar'i, yaitu tangga menuju Allah swt. dan dia juga adalah jalan menuju keridhaan-Nya. Islam tidak dapat ditegakkan kecuali dengan ilmu. Islam beredar dan diberitakan di tengah-tengah masyarakat dengan ilmu, dan umat Islam adalah orang yang berilmu, karena semua aturan dan ajaran yang terkandung dalam Islam didasarkan dan didasarkan pada ilmu. Al-Qur'an dari awal sampai akhir adalah ilmu yang banyak mengandung pelajaran yang sangat penting dan berharga bagi kita, dan kita tidak boleh membicarakan agama ini kecuali dengan ilmu. Ilmu memiliki kedudukan yang tinggi dalam Islam. Karena itu orang yang berilmu menempati kedudukan yang tinggi di sisi Allah SWT. Semua umat Islam diwajibkan untuk menuntut ilmu agar imannya tidak menyimpang, ibadahnya benar, dan perilakunya sesuai dengan syariat. Menuntut ilmu merupakan salah satu kewajiban bagi setiap muslim selama hayat masih dikandung badan